2019
DOI: 10.1016/j.arabjc.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modelling, synthesis, and antimalarial potentials of curcumin analogues containing heterocyclic ring

Abstract: The molecular modelling approach was applied to a series of nineteen curcumin analogues to find the possible PfRIO2 kinase inhibitory action. A putative active site in flexible loop (S1) of PfRIO2 kinase was explored computationally to recognize the molecular basis of ligands binding. The ligands (curcumin analogues; 3a-3s) were well accommodated in the selected active site (S1) due to their higher molecular size and length. Further all these synthesized compounds (3a-3s) were evaluated for their in vitro anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Belaji et al reported the molecular modelling, synthesis, and antimalarial potentials of curcumin analogues containing pyrazole ring. The compound 485 showed the most significant result, with maximum schizonticidal (IC 50 = 1.48 μM) and parasiticidal activities (MKC; 3.87 = μM) [ 379 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Belaji et al reported the molecular modelling, synthesis, and antimalarial potentials of curcumin analogues containing pyrazole ring. The compound 485 showed the most significant result, with maximum schizonticidal (IC 50 = 1.48 μM) and parasiticidal activities (MKC; 3.87 = μM) [ 379 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…In combination with their favorable drug-like properties, privileged structures or scaffolds are widely used in rational drug design to find new lead compounds or drug candidates [1,2,3]. Pyrazole derivatives represent one of the most active classes of compounds that possess a wide spectrum of biological activities, including antibacterial and antifungal [4,5], antitumor [6,7], anti-inflammatory and analgesic [8,9], antitubercular [10], antiviral [11,12], anti-Alzheimer’s [13,14], α-glucosidase inhibitory [15], anti-diabetic [16], antileishmanial [17,18], anti-malarial [19], radioimaging [20], acaricidal and insecticidal [21,22] activities. As a privileged scaffold, pyrazole has been recently widely used in the design of anticancer agents for a multiple of tumor targets [23].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the group investigated Curcumin semicarbazones anti-proliferative and antioxidant activity; and identified that semicarbazones electronwithdrawing group as well as imine carbonyl and phenoxyl radical impart curcumin semicarbazone its anti-oxidant potential (Dutta et al 2005). Furthermore, the compound has been tested for its anti-inflammatory, antinociceptive, cyclooxygenase-2 inhibition, carbonic-anhydrase inhibition, and anti-malarial (Ahmed et al 2018a, b) (Ahmed et al 2018a, b-2) (Balaji et al 2019). To assess its cytotoxic potency and assert the claims put forth by the in silico analysis, the ligands were screened via SRB assay in human CRC cell line HCT 116 and semicarbazide curcumin indicated a sevenfold better activity than curcumin and also comparable dose-dependent cell viability at lower concentrations when compared to Doxorubicin (Table 5 and Fig.…”
Section: Discussionmentioning
confidence: 99%